Pengaruh Penerapan Tri Core Breastfeeding Models Terhadap Kemauan Ibu Menyusui Di Rsu Wijayakusuma - Rahma Nurin Saraya; Raden Maria Veronika Widiatrilupi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
One of the factors influencing a mother’s breastfeeding willingness is her level of knowledge. Low exclusive breastfeeding coverage rates may result in infants not receiving adequate nutrition. Thus, exclusive breastfeeding is strongly recommended to support the growth and development process of children from an early age. Strategies to increase the coverage of exclusive breastfeeding include breastfeeding education, social support, and improving maternal self-confidence, all of which are incorporated within the Tri Core Breastfeeding Models approach. This model is a practice guide based on health promotion strategies focused on mothers to increase awareness of the importance of exclusive breastfeeding. This study aims to examine The Effect of Tri Core Breastfeeding Models on the Willingness of Breastfeeding Mothers at Wijayakusuma General Hospital in 2025. The research was conducted from May to June 2025 at RSU Wijayakusuma in Kebumen using a pre-experimental method with a posttest-only control group design. A total of 30 respondents participated in the study, and data were collected using the Infant Feeding Intentions Scale (IFIS), which had been tested for validity and reliability. Data were analyzed using an independent t-test with a 95% significance level. The results of the analysis showed that the significance value of P=0.000, which indicated a significant difference after the intervention. Thus, the implementation of the Tri Core Breastfeeding Models has been proven to increase mothers’ breastfeeding willingness. It is recommended that this approach be integrated into midwifery care services to support the success of exclusive breastfeeding programs.